Post-Truth and Hoaxes: Instagram's Fact Checking of Content on Vaccines in Indonesia - Ayu, Aulia Suminar; Haryono, Novita; Arzil, Andrine Prima Afneta; Hastjarjo, Sri; ., Widyantoro (KnE Social Sciences, 2022)
The interconnected world creates a post-truth society. Everyone stands for their truth, whether it has a strong basis in facts or not. The COVID-19 pandemic created uncertainty due to its novelty. Tempo is one of Indonesia’s media outlets and it is affiliated with the International Fact Checking Network, which is committed to promoting media literacy. This article aimed to conduct a framing analysis about how Tempo combats hoaxes about vaccines in Indonesia through its Instagram account. Data were collected from Tempo’s Instagram postings related to vaccines in Indonesia from January 2021 to September 2021 (n = 25). Gamson-Mogdialni’s framing analysis was used in this study. Aspects that were analysed in this framing analysis included metaphors, examples, catchphrases, depictions, visual images, roots, and appeals to principles. According to the results, most of the hoax information referred to health workers, the government, and conspiracy theories. Moreover, the results suggested that a fact checking system could provide a reference for mass media framing, which could increase public trust about an issue, especially COVID-19 vaccine safety. Keywords: infodemic, fact-checking, post-truth, framing analysis, Instagram